Morbilidad bucodental en músicos de bandas de porro del departamento de Córdoba - Alex Olmedo Panzza-Negrete; Jaime Alberto Castaño-Núñez; Luis Carlos Pedraza-Castillo; Manuel Cabrales-Marrugo (Universidad de Antioquia, 2000)
lt was examined 79 lolklor band musicians. 47 musicians played wind musical instruments with cup ernbouch ure, ]6 musicians with reed embouchure and 16 drumers. The study describe the bucodental health situation 01 the rural poblation and musically empine. that abuses 01the instruments ejecution and do not known the lesions in oral cavity that are caused by the indiscriminate use 01 these instruments; lesions which are diflerent depending on the embouchure type. The drumers musicians were taken as a control group. Data collection was made through clinical examination that include occlusal measures registration, decay index, periodontal index, solt tissues exploration and musicians oral hy~ giene habits indagation. Analysis was made in EPIINFO 6.04b, 1997. lt was lound a decay index 01 10.2 and decay prevalence 0188.]%. The general ESI was (66, 1.9) and the specilic ESI was (70, 2.]). lt was identified a well rounded, white and delormity lesions in the musicians lips 01 those who play wind instruments with cup 01mouthpiece. Theprevalence was 82.6%.